2021
DOI: 10.1371/journal.pone.0250336
|View full text |Cite
|
Sign up to set email alerts
|

Health anxiety, coping mechanisms and COVID 19: An Indian community sample at week 1 of lockdown

Abstract: It is critical to gain an understanding of the impact of the COVID 19 pandemic and the associated lockdown restrictions on the psychological, social and behavioural functioning of the general public, in order to inform public health promotion and future health service resource allocation. This cross-sectional study, completed during week 1 of lockdown in India, reports on data from 234 participants using an online survey. Data regarding health anxiety, coping mechanisms and locus of control was collected. Stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 60 publications
2
15
0
Order By: Relevance
“…Coping strategies have the main strength, namely being able to manage negative thoughts into positive ones or change bad conditions becomes better (Pons, Viladrich, Ramis, & Polman, 2018;Borkoles et al, 2018). Previous studies also support the results of this study, where coping strategies are an effective method for a person to control and reduce stress levels (Bamuhair et al, 2015) and anxiety (Millar et al, 2021). In addition, using coping strategies with properly will be an effective pedagogical tool to reduce stress and anxiety of students when studying both offline and online class (Basith et al, 2021).…”
Section: Impact Of Coping Strategies On Anxietysupporting
confidence: 83%
See 1 more Smart Citation
“…Coping strategies have the main strength, namely being able to manage negative thoughts into positive ones or change bad conditions becomes better (Pons, Viladrich, Ramis, & Polman, 2018;Borkoles et al, 2018). Previous studies also support the results of this study, where coping strategies are an effective method for a person to control and reduce stress levels (Bamuhair et al, 2015) and anxiety (Millar et al, 2021). In addition, using coping strategies with properly will be an effective pedagogical tool to reduce stress and anxiety of students when studying both offline and online class (Basith et al, 2021).…”
Section: Impact Of Coping Strategies On Anxietysupporting
confidence: 83%
“…Recent studies have reported that several factors that cause the increment of anxiety levels are online learning which has various obstacles is a trigger for anxiety symptoms in students (Basheti, Mhaidat & Mhaidat, 2021). Several factors caused the level of anxiety during the pandemic increase drastically, were students were afraid of contracting COVID-19, students had to undergo isolation/lock down (Millar et al, 2021), or the difficulty of carrying out physical education learning online (Jumareng et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The third C-'connectedness' addresses the innate human need for social support. Millar et al (2021) studied the impact of the COVID-19 pandemic and lockdown restrictions in India on the psychological, social, and behavioural changes of the public. The study used cross-sectional data of 234 respondents collected after the completion of the first week of lockdown.…”
Section: Psychology Of Copingmentioning
confidence: 99%
“…However, a high level of compliance to undergo CXR examination in this study was probably due to worry about long COVID among the population after a serious COVID-19 outbreak recently subsided [ 36 ]. In addition to TB detection, they might expect CXR to detect the residual effects of COVID-19 and thus they had high compliance.…”
Section: Discussionmentioning
confidence: 99%